An insight in the reproductive biology of Therophilus javanus (Hymenoptera, Braconidae, and Agathidinae), a potential biological control agent against the legume pod borer (Lepidoptera, Crambidae) - Souna, D.A.; Bokonon-Ganta, A.H.; Ravallec, M.; Cusumano, A.; Pittendrigh, Barry Robert; Volkoff, A.N.; Tamò, Manuele (Hindawi Limited, 2017)
Therophilus javanus is a koinobiont, solitary larval endoparasitoid currently being considered as a biological control agent against the pod borer Maruca vitrata, a devastating cowpea pest causing 20–80% crop losses in West Africa. We investigated ovary morphology and anatomy, oogenesis, potential fecundity, and egg load in T. javanus, as well as the effect of factors such as age of the female and parasitoid/host size at oviposition on egg load.The number of ovarioles was found to be variable and significantly influenced by the age/size of the M. vitrata caterpillar when parasitized. Egg load also was strongly influenced by both the instar of M. vitrata caterpillar at the moment of parasitism and wasp age.The practical implications of these findings for improving mass rearing of the parasitoid toward successful biological control of M. vitrata are discussed.